Pengaruh Kedisiplinan Kerja, Motivasi Kerja, Manajemen Talenta, Manajemen Pengetahuan dan Kompensasi Terhadap Kinerja Karyawan Ekspedisi di Kota Batam - Ompusunggu, Sandoko; Fatyandari, Adi Neka (REVITALISASI : Jurnal Ilmu Manajemen, 2023)
This research discusses the influence of work discipline, work motivation, talent management, knowledge management and compensation on the performance of expedition employees in Batam City. This research aims to find the relationship between each independent variable and the dependent variable. The research method uses quantitative by using Google Form as a tool for collecting data. The data used are respondents from expedition company employees in Batam City totaling 300 employees. The SPSS program is the application used to test research data. The research results explain that work discipline influences employee performance, work motivation influences employee performance, talent management influences employee performance, knowledge management influences employee performance and compensation influences employee performance.